Influence of Nitrogen Application Rates on Yield and Yield Attributes of Long Duration Varieties of Cassava (Manihot esculenta Crantz) - Kumar, J. Suresh; Riswana, R.; Akash, A. U.; Sunitha, S. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was carried out at ICAR- Central Tuber Crops Research Institute (CTCRI), Sreekariyam, Thiruvananthapuram, Kerala, India to investigate the effect of different nitrogen application rates on yield and yield attributes of two long-duration cassava varieties during March, 2021 to February, 2022. The experiment was set up in Factorial Randomized Block Design (FRBD) with three replications involving two factors- two cassava varieties (Sree Pavithra and Sree Reksha) and five different nitrogen application rates (0%, 25%, 50%, 100% and 125%) of recommended nitrogen dose of 100 kg ha-1. The study revealed that the application of super optimal dose of nitrogen (125%RD of nitrogen @ 125 kg ha-1) significantly increased the yield (52.61 t ha-1) and yield attributes namely number of tubers (3.55) plant-1, average lenth of tuber (25.48 cm), average diameter of the tuber (12 cm) and average tuber yield plant-1 (4.24 kg) in cassava. Also, super optimal dose of nitrogen positively influenced SPAD 502 chlorophyll meter reading (45.13), leaf chlorophyll a content (1.52, 1.72 mg g-1), chlorophyll b (0.64, 0.72 mg g-1) content and total chlorophyll content (2.20, 2.49 mg g-1), leaf carotene content (0.42, 0.48 mg g-1) in V1 (Sree Pavithra) V2 (Sree Reksha) respectively. Super optimal level of nitrogen positively influenced nitrogen content in leaf,stem and tuber along with phosphorous and potash content in both varieties of cassava.